EFEKTIVITAS EKSTRAK BUNGA PEPAYA EFEKTIVITAS EKSTRAK BUNGA PEPAYA (CARICA PAPAYA) SEBAGAI BIOINSEKTISIDA TERHADAP KEMATIAN LALAT: EFEKTIVITAS EKSTRAK BUNGA PEPAYA (CARICA PAPAYA) SEBAGAI BIOINSEKTISIDA TERHADAP KEMATIAN LALAT - Nurafni Maftukhah; Asputri Wulandari (IKesT Muhammadiyah Palembang, 2026)
Background : Flies (Diptera) are are ubiquitous insects that pose significant risks to human health by transmitting diseases. Controlling fly populations is critical to mitigating these risks. Papaya flowers (Carica papaya) contain bioactive compounds with potential insecticidal properties, offering an eco-friendly alternative to synthetic insecticides. Research Objective: This study aimed to determine the effect of Carica papaya flower extract concentrations on fly mortality. Research Method: A true experimental design was employed with four treatment groups (each replicated six times). Flies were exposed to spray treatments of papaya flower extract at concentrations of 0% (control), 25%, 50%, and 75% (15 flies per group). Mortality rates were recorded and analyzed to evaluate the extract’s bioinsecticidal efficacy. Results: 25% concentration: Average mortality of 1.3 flies (total 8 flies), 50% concentration: Average mortality of 2.5 flies (total 15 flies), 75% concentration: Average mortality of 3.8 flies (total 23 flies). Mortality increased proportionally with extract concentration, demonstrating a dose-dependent effect. Conclusion: Papaya flower extract significantly induces fly mortality, with higher concentrations yielding greater efficacy. These findings support its potential as a natural bioinsecticide for fly population control.